Basic Beliefs, the Embryo Rescue Case, and Single-Issue Voting: A Response to Dustin Crummett - McNabb, Tyler; DeVito, Michael (The National Catholic Bioethics Quarterly, 2021)
In this essay, we respond to Dustin Crummett’s argument that one cannot consistently appeal to body count reasoning to justify being a single-issue pro-life voter if one is also committed to the usual response to the embryo rescue case. Specifically, we argue that a modified version of BCR we call BCR* is consistent with the usual response. We then move to address concerns about the relevance of BCR* to Crummett’s original thesis.
GSCC: 0000000

Cognitive Science of Religion and Classical Theism: A Synthesis - McNabb, Tyler Dalton; DeVito, Michael (Religions, 2022)
Launonen and Mullins argue that if Classical Theism is true, human cognition is likely not theism-tracking, at least, given what we know from cognitive science of religion. In this essay, we develop a model for how classical theists can make sense of the findings from cognitive science, without abandoning their Classical Theist commitments. We also provide an argument for how our model aligns well with the Christian doctrine of general revelation.
0 citations (Crossref) [2022-09-21]

Divine foreknowledge and human free will: Embracing the paradox - DeVito, Michael; McNabb, Tyler Dalton (International Journal for Philosophy of Religion, 2021)
0 citations (Crossref) [2022-09-21] GSCC: 0000000

Has Oppy Done Away with the Aristotelian Proof? - McNabb, Tyler; DeVito, Michael (The Heythrop Journal, 2020)
0 citations (Crossref) [2022-09-21] GSCC: 0000000

Ockham on the Side of the Angels: Why a Classical Theist Shouldn't be Moved by Oppy's Argument from Simplicity - McNabb, Tyler; DeVito, Michael (New Blackfriars, 2022)
0 citations (Crossref) [2022-09-21]

The evolutionary argument against naturalism: a Wittgensteinian response - DeVito, Michael; McNabb, Tyler (International Journal for Philosophy of Religion, 2022)
In this essay, we put forth a novel solution to Plantinga’s Evolutionary Argument Against Naturalism, utilizing recent work done by Duncan Pritchard on radical skepticism. Key to the success of Plantinga’s argument is the doubting of the reliability of one’s cognitive faculties. We argue (viz. Pritchard and Wittgenstein) that the reliability of one’s cognitive faculties constitutes a hinge commitment, thus is exempt from rational evaluation. In turn, the naturalist who endorses hinge epistemology can deny the key premise in Plantinga’s argument and avoid the dilemma posed on belief in the conjunction of naturalism and evolution.
0 citations (Crossref) [2022-09-21]